Protein Quakes in Redox Metalloenzymes: Clues to Molecular Enzyme Conductivity Triggered by Binding of Small Substrate Molecules - Henrik Bohr; Irene Shim; Jens Ulstrup; Xinxin Xiao (ChemistryOpen)
Abstract Multicentre redox metalloproteins undergo conformational changes on electrochemical surfaces, or on enzyme substrate binding. The two‐centre copper enzymes, laccase (Type I and TypeII/III Cu) and nitrite reductase (CuNIR) (Type I and Type II Cu) are examples. With some exceptions, these enzymes show no non‐turnover voltammetry on Au(111)‐surfaces modified by thiol based self‐assembled molecular monolayers, but dioxygen or nitrite substrate triggers strong electrocatalytic signals. Scanning tunnelling microscopy also shows high conductivity only when dioxygen or nitrite is present. Atomic force microscopy shows constant CuNIR height but pronounced structural expansion in the electrocatalytic range on nitrite binding. We have recently offered a rationale, based on ab initio quantum chemical studies of water/nitrite substitution in a 740‐atom CuNIR fragment. Presently we provide much more detailed structural assignment mapped to single‐residue resolution. NO2−‐binding induces both a 2 Å Cu−Cu distance increase, and pronounced frontier orbital delocalization strongly facilitating ET between the Cu regions. The conformational changes transmit from the catalytic Type II centre to the electron inlet Type I centre, via the His129‐Cys130 ligands, and via Type I–Cys130 or Type I‐His129 ending at Type II Asp92. The ET patterns are reflected in different atomic Mulliken charges in the water and nitrite CuNIR fragment.